Transforming Tajikistan : state-building and Islam in post-Soviet Central Asia - Thibault, Hélène (International library of Central Asian studies, 2018)
"Tajikistan is a key state in Central Asia, and will become crucial to the regional power balance as it transitions away from Soviet government systems and responds to the rise of Chinese financial power alongside the continuing presence of Russian military might and instability in neighboring Afghanistan. This book demonstrates how the Soviet atheist legacy continues to influence current state structures, the regulation of religion, the formation of national identities, and the understanding of the place of religion in society. Helene Thibault focuses on the differences between secular nationhood in Tajikistan, and an increasingly popular and influential Muslim identity. Featuring extensive and original primary-source material, including 12 months of ethnographic fieldwork, Thibault demonstrates the profound and lasting influence of Soviet power structures and attitudes, and how secular and religious identities clash in a context of tightening authoritarianism."--Bloomsbury Publishing